2016
DOI: 10.1007/s13149-016-0519-9
|View full text |Cite
|
Sign up to set email alerts
|

Nouvel aperçu sur l’écologie larvaire d’Anopheles coluzzii Coetzee et Wilkerson, 2013 dans l’estuaire du Wouri, Littoral-Cameroun

Abstract: Malaria vectors control is essentially based on the use of insecticides against adult mosquitoes. However because of the development of resistance to insecticides, there is now a renewed interest in the management of larval sources. The aim of the present study was to map and characterize the breeding sites of Anopheles coluzzii in the Wouri river estuary in Cameroon. Larval surveys were carried out between December 2013 and August 2014 in rural areas on the island of Manoka and urban area in Youpwe at Douala.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
4
10
0
Order By: Relevance
“…larvae were found to colonize a large number of habitats including temporary water collections, permanent sites and artificial habitats. This was in accordance with the high adaptation capacity of the species in urban settings [22, 4850]. An.…”
Section: Discussionsupporting
confidence: 83%
“…larvae were found to colonize a large number of habitats including temporary water collections, permanent sites and artificial habitats. This was in accordance with the high adaptation capacity of the species in urban settings [22, 4850]. An.…”
Section: Discussionsupporting
confidence: 83%
“…Two recent studies document utilization of boats for breeding by Anopheles coluzzii (initially the M form of An. gambiae sensu lato) in two fishing communities within the Wouri river estuary near the port of Duala in Cameroon [53, 54]. Data in this article corroborate these findings, albeit with respect to An.…”
Section: Discussionsupporting
confidence: 75%
“…gambiae s.s., which was the only Anopheles species identified on Mageta Island. Mbida et al [54] explain the phenomenon of An. coluzzii breeding in boats, among other man-made habitats, as an adaptation to utilizing artificial habitats when natural ones become rare.…”
Section: Discussionmentioning
confidence: 99%
“…Anopheles coluzzii ecological success is illustrated by its phenotypic plasticity 34 , 77 , 78 . At the larval stage, this mosquito exhibits an extraordinary adaptability to develop in a great variety of breeding sites 22 , 79 – 82 , with a preference for more permanent ones 83 . Our study confirmed the wide range of aquatic conditions where this species can lay and develop, in coastal and urban settings of Central Africa.…”
Section: Discussionmentioning
confidence: 99%